Araucaria schmidii de Laubenfels - Sarrailh, Jean-Michel; Chauvin, Jean-Paul; Gateblé, Gildas; Dumontet, Vincent; Pieters, Romuald (BOIS & FORETS DES TROPIQUES, 2007)
Le résumé est disponible dans le fichier PDF de l'article.